MEMBANGUN MINAT BERWIRAUSAHA MELALUI MOTIVASI, PENDIDIKAN KEWIRAUSAHAAN DAN KEPRIBADIAN - Putri Gesit Purwani Sari; Muinah Fadhilah; Bernadetta Dian Septi Maharani (Magister Manajemen STIE Bank BPD Jateng, 2021)
This study is aimed at recognizing the motivational, entrepreneurial ducation and personality has on entrepreneurial interests. The study consists of three dependent variables, which are motivational, entrepreneurial education, personality and one independent variable in entrepreneurship intrest. The population in the study are students of Sarjanawiyata university economics students with a sample of over 100 research model respondents using a quantitative analysis. Results show that a positive influence between motivations for entrepreneurial interests, there is no influence between entrepreneurial education variables ovr entrepreneurial interests, there is a positive influence personality between entreprnurial interests.